Counseling Skills Training for Service Officers of Women's Empowerment and Child Protection Consultation Institute (LKP3A)in Pekalongan Regency - Esti Zaduqisti; Purnomo Rozak; Teddy Diyatmika; Syamsul Bakhri (Islamic Studies Journal for Social Transformation, 2019)
LKP3A counselor in terms of quality and quantity is still very lacking. One of the indicationsis there are still many unskillful bachelor degree graduates that work as counselors. Thus,there is a need for assistance and empowerment to meet the needs of the community. Thiscommunity empowerment program aims to improve knowledge and counseling skills thatare still relatively minimal for mentors at LKP3A Fatayat Nadhalatul Ulama Pekalongan. Thisresearch is a participatory action research (PAR) with a qualitative approach. This researchwas carried out for 1 year in the NU building in Pekalongan. The subjects of this study weredivided into two community categories namely the Core Trainer Team (TIP) and LKP3AWomen's Citizens (WP). Counseling skills training is carried out through three activities,namely planning, implementation, and evaluation monitoring activities. The results of thisresearch show that after LKP3A counselors received training and mentoring, it showed manychanges, including being able to understand ethical principles for counseling and payingattention to risk management; able to bring up a friendly attitude; empathize; want to listento clients; understand and appreciate individual differences. The counselor provides servicesbased on these differences. The focus on the client is greater. The counselor understands herposition as a counselor, able to integrate theory into counseling practice, able to evaluate thecourse of counseling both in the process and results.